2013
DOI: 10.4103/0971-6203.116364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between 5 mm and 7.5 mm collimators in CyberKnife radiosurgery for trigeminal neuralgia

Abstract: Trigeminal neuralgia (TN) is treated in CyberKnife (Accuray Inc, Sunnyvale, USA) with the 5 mm collimator whose dosimetric inaccuracy is higher than the other available collimators. The 7.5 mm collimator which is having less dosimetric uncertainty can be an alternative for 5 mm collimator provided the dose distribution with 7.5 mm collimator is acceptable. Aim of this study is to analyze the role of 7.5 mm collimator in CyberKnife treatment plans of TN. The treatment plans with 5 mm collimators were re-optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that small collimator scan achieves high dose conformity and steep dose gradient, while large collimators tend to minimize the total monitor units (MUs) and treatment beams. [ 16 17 ] With a combination of two collimators, the total MUs in the treatment plan can also be reduced by an average of 31% compared to the single collimator. [ 18 ] Such improvements in prostate plan dosimetry and treatment efficiency are immediately realized by using the more advanced IRIS variable collimator which was introduced in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that small collimator scan achieves high dose conformity and steep dose gradient, while large collimators tend to minimize the total monitor units (MUs) and treatment beams. [ 16 17 ] With a combination of two collimators, the total MUs in the treatment plan can also be reduced by an average of 31% compared to the single collimator. [ 18 ] Such improvements in prostate plan dosimetry and treatment efficiency are immediately realized by using the more advanced IRIS variable collimator which was introduced in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…17 Thought to relieve the symptoms of some patients in the early stage, those antiepileptic drugs have many side effects and the patient would resist against it with time. The other choices are those ablative procedures, such as glycerol injections, 18 radiosurgery (gamma knife), 19-23 radiofrequency rhizotomy, [24][25][26][27][28] and so on. Partial sensory rhizotomy has now rarely been performed for TN because of its higher recurrence and intolerable dysesthesia due to nerve damage.…”
mentioning
confidence: 99%
“…20 However, large dose heterogeneity inside a target is often acceptable in SRS/SRT, such as in CyberKnife and Gamma Knife radiosurgery in which the normalization of dose distributions to low isodoses can often be seen in trigeminal neuralgia treatments to improve target conformity and OAR dose sparing. 21,22 F I G U R E 1 3 Absolute dose difference in (a) average maximum dose and (b) average mean dose to each OAR between VMAT and 3-arc CODA-iABC techniques (N = 7). Positive values indicate that 3-arc CODA-iABC plans achieve better dose sparing to an OAR when comparing to VMAT plans.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased MLC aperture margins have been shown to have a sharper dose gradient outside the target volume and a narrower shoulder of target DVHs, but with a cost in target dose homogeneity 20 . However, large dose heterogeneity inside a target is often acceptable in SRS/SRT, such as in CyberKnife and Gamma Knife radiosurgery in which the normalization of dose distributions to low isodoses can often be seen in trigeminal neuralgia treatments to improve target conformity and OAR dose sparing 21,22 …”
Section: Discussionmentioning
confidence: 99%